Exome-Wide Association Study Identifies East Asian-Specific Missense Variant MTHFR C136T Influencing Homocysteine Levels in Chinese Populations RH: ExWAS of tHCY in a Chinese Population - Liu, Tianzi; Momin, Mohetaboer; Zhou, Huiyue; Zheng, Qiwen; Fan, Fangfang; Jia, Jia; Liu, Mengyuan; Bao, Minghui; Li, Jianping; Huo, Yong; Liu, Jialin; Zhang, Yaning; et al. (Frontiers in Genetics, 2021)
Plasma total homocysteine (tHCY) is a known risk factor of a wide range of complex diseases. No genome scans for tHCY have been conducted in East Asian populations. Here, we conducted an exome-wide association study (ExWAS) for tHCY in 5,175 individuals of Chinese Han origin, followed by a replication study in 668 Chinese individuals. The ExWAS identified two loci, 1p36.22 (lead SNP rs1801133, MTHFR C677T) and 16q24.3 (rs1126464, DPEP1), showing exome-wide significant association with tHCY (P < 5E-7) and both loci have been previously associated with tHCY in non-East Asian populations. Both SNPs were replicated in the replication study (P < 0.05). Conditioning on the genotype of C677T and rs1126464, we identified a novel East Asian-specific missense variant rs138189536 (C136T) of MTHFR (P = 6.53E-10), which was also significant in the replication study (P = 9.8E-3). The C136T and the C677T variants affect tHCY in a compound heterozygote manner, where compound heterozygote and homozygote genotype carriers had on average 43.4% increased tHCY compared with other genotypes. The frequency of the homozygote C677T genotype showed an inverse-U shape geospatial pattern globally with a pronounced frequency in northern China, coincided with the high prevalence of hyperhomocysteinemia (HHCY) in northern China. A logistic regression model of HHCY status considering sex, age and the genotypes of the 3 identified variants reached an AUC value of 0.74 in an independent validation cohort. These genetic observations provide new insights into the presence of multiple causal mutations at the MTHFR locus, highlight the role of genetics in HHCY epidemiology among different populations, and provide candidate loci for future functional studies.